Currency and Credit in a Private Information Economy - Townsend, Robert M. (Journal of Political Economy, 1989)
In an environment with private information, spatial separation, and limited communication, a currency-like object and more standard named credits can be distinguished. The credit objects can be used among agents in an enduring relationship, that is, among agents with known trading histories, whereas the currency-like object must be used among relative strangers. In this environment, collectively determined Pareto-optimal rules make the level of the currency-like object and the mix of currency to named credits responsive to individual needs and to economywide states. Total indebtedness is determined by the number of lenders, that is, by preference or demand shock, and the mix of currency to credits is determined by transaction patterns among the agents.